LITHOSTRATIGRAPHY AND FACIES ARCHITECTURE OF THE OLIGOCENE CONGLOMERATES AT MONTE PAREI (FANES. DOLOMITES, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
The only occurrence of Tertiary (Oligocene) sediments in the Dolomites at Monte Parei results from a complex tectonic and sedimentary history. The Tertiary marine clastic succession is sealing the Dinaric (Late Cretaceous to Paleogene) deformed basement. The basin-fill can be differentiated into four lithofacies which show extensive lateral interfingering: ,local scarp breccias with giant blocks (facies A), chaotic breccias of debris flow origin (facies B), balanid and shell coquina beds (facies C) and conglomeratic grain and debris flows with sandstone intercalations (facies D). Transport directions (imbricate clasts and cross bedding) and petrographic composition indicate two different source areas. Sediments of facies B were shed from a structural high in the SW, while carbonate-siliciclastic debris of facies C and D originated from a pebbly or rocky shore in the N. Lithofacies and facies interrelationships clearly indicate the control by synsedimentary tectonic activity. Neoalpine closure of the basin by overthrusting lead to the preservation of the sediments.